2021
DOI: 10.1039/d1nr03864h
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopical monolayer films of ordered arrays of gold nanoparticles as SERS substrates for in situ quantitative detection in aqueous solutions

Abstract: In this work, macroscopical monolayer films of ordered arrays of gold nanoparticles (MMF-OA-Au NPs) are successfully prepared at the interfaces of toluene-diethylene glycol (DEG) with a water volume fraction of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 62 publications
3
19
0
Order By: Relevance
“…Due to the poor solubility of citrate ions in the DEG phase, the remaining citrate ions can quickly transfer from the oil phase into the DEG phase containing a proper amount of water (10% v/v) during the interfacial self-assembly to reduce the residual negative charges among NPs (Scheme 1d). 37 Therefore, high- quality LAMFs of Au@Ag NPs can be fabricated at the interface of toluene−DEG containing a proper amount of water. Three types of high-quality LAMF-HCP-Au 5.5 @Ag m NPs (Figures 3, S5 and S6) were successfully fabricated by our improved self-assembly method, 37 in which the ligands on the surfaces of these as-prepared Au 5.5 @Ag 5.25 NPs have to be exchanged from citrate into OLA using the phase transfer technology.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the poor solubility of citrate ions in the DEG phase, the remaining citrate ions can quickly transfer from the oil phase into the DEG phase containing a proper amount of water (10% v/v) during the interfacial self-assembly to reduce the residual negative charges among NPs (Scheme 1d). 37 Therefore, high- quality LAMFs of Au@Ag NPs can be fabricated at the interface of toluene−DEG containing a proper amount of water. Three types of high-quality LAMF-HCP-Au 5.5 @Ag m NPs (Figures 3, S5 and S6) were successfully fabricated by our improved self-assembly method, 37 in which the ligands on the surfaces of these as-prepared Au 5.5 @Ag 5.25 NPs have to be exchanged from citrate into OLA using the phase transfer technology.…”
Section: Resultsmentioning
confidence: 99%
“…37 Therefore, high- quality LAMFs of Au@Ag NPs can be fabricated at the interface of toluene−DEG containing a proper amount of water. Three types of high-quality LAMF-HCP-Au 5.5 @Ag m NPs (Figures 3, S5 and S6) were successfully fabricated by our improved self-assembly method, 37 in which the ligands on the surfaces of these as-prepared Au 5.5 @Ag 5.25 NPs have to be exchanged from citrate into OLA using the phase transfer technology. It is found that the resulting LAMF-HCP-Au 5.5 @ Ag 5.25 NPs on the surface of the DEG phase show a fuchsia color and their area can be up to 30 cm 2 , as shown in the optical photograph (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations